2017
DOI: 10.1177/0957650916688398
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction mechanisms for the inclined leading edge vaned diffuser in a centrifugal fan

Abstract: An experimental and numerical study to explore the noise reduction mechanism for the inclined leading edge vaned diffuser in centrifugal fans is described. Inclined leading edge vaned diffuser is useful in improving fan performance, increasing operating range, and reducing fan noise. The generation of fan noise is related to the pressure fluctuation on the diffuser vane surface, particularly the leading edge. Numerical results show that pressure fluctuation on the inclined leading edge vaned diffuser surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Wang [16] et al designed an impeller meridian shape, and with the help of numerical simulation methods, they proved that the aerodynamic performance of the fan has been improved and the velocity Processes 2024, 12, 353 3 of 21 distribution is more reasonable. Qi [17] et al conducted experimental and numerical studies on the noise reduction mechanism of tilted leading-edge blade diffusers for centrifugal fans, which showed that the tilted leading-edge diffuser is essential for improving the performance of the fan and reducing the noise of the fan.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [16] et al designed an impeller meridian shape, and with the help of numerical simulation methods, they proved that the aerodynamic performance of the fan has been improved and the velocity Processes 2024, 12, 353 3 of 21 distribution is more reasonable. Qi [17] et al conducted experimental and numerical studies on the noise reduction mechanism of tilted leading-edge blade diffusers for centrifugal fans, which showed that the tilted leading-edge diffuser is essential for improving the performance of the fan and reducing the noise of the fan.…”
Section: Introductionmentioning
confidence: 99%